The Effectiveness of Acceptance and Commitment Therapy (ACT) on Perceived stress & Psycho-Somatic Signes & emotional distress in IVF infertile women - Zohrehvandi, Zahra; Babakhani, Narges; Taheri, Afsaneh (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to investigate the effect of acceptance and commitment therapy on perceived stress, psychosomatic symptoms and emotional distress in women undergoing IVF infertility treatment. Methods: The method of this research is quasi-experimental and is a pretest-posttest design with a control group. The statistical population in this study included women undergoing IVF infertility treatment who referred to infertility treatment centers and clinics in Tehran in 2019. Cohen’s table was used to determine the sample size. According to this table, with an effect size of 0.5 and a power of 0.76 with an alpha of 0.05, the sample size of 30people was estimated and the available sampling method was selected, in which 15 people were randomly assigned in each group (experimental and control). Cohen et al.’s Perceived Stress Questionnaire (1983), Lovibond & Lovibond LacourtAnxiety, Stress and Depression (1995), Lacourt Psychosomatic Symptoms (2013), and Acceptance and Practice Version II (2011) were used to collect information in two stages: pre-test and post-test. The experimental group underwent acceptance and commitment group therapy Based on Hayes therapy package (2002), in 8 sessions of 90 minutes, while the control group did not receive any intervention. SPSS-22 software was used to evaluate the results. Results: The results of repeated-measures analysis of variance showed that acceptance and commitment based therapy is effective in reducing perceived stress, psychosomatic symptoms and emotional distress in women undergoing IVF infertility treatment (P <0.001). Also, the results were stable in the follow-up phase. Conclusion: It is recommended that therapists and counselors of infertility treatment centers use acceptance and commitment therapy in infertility clinics to reduce the needs and psychological problems of infertile women undergoing IVF treatment.